Energy values and metabolizability of lipid sources of plant and animal origin in the diet of Japanese quail - Valentim, Jean Kaique (2023)
The objective of this study was to determine the energy values and metabolizability of different lipid sources in the diet of Japanese quail at the laying phase. The quail were distributed in a completely randomized design with ten replications of seven poultry per treatment, totaling six treatments: basal feed (control) and basal feed containing 10% soybean oil, corn oil, canola oil, sunflower oil, and poultry fat. The values of nitrogen-corrected apparent metabolizable energy (AMEn) and the metabolizability coefficient (MC%) were evaluated. No significant difference was found between the different lipid sources for AMEn (kcal/kg) and MC (%). The value of metabolizable energy corrected for nitrogen for soybean oil was 8,790 kcal/kg; 8,773 kcal/kg for corn oil; 8,784 kcal/kg for canola oil; 8,788 kcal/kg for sunflower oil; and 8,681 kcal/kg for poultry fat in laying Japanese quail. The digestibility coefficients were 93.88% for soybean oil, 93.53% for corn oil, 93.32% for canola oil, 93.74% for sunflower oil, and 93.06% for poultry fat.